Inductive Method Improves Elementary Students Short Story Writing Performance: Metode Induktif Meningkatkan Kinerja Penulisan Cerpen Siswa Sekolah Dasar - Nikmatu Qurota A'yun; Ahmad Nurefendi Fradana, M.Pd. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Writing short stories is a complex language skill that requires the integration of imagination, narrative structure, and linguistic competence, yet many elementary students experience difficulties in expressing ideas in written form. Specific Background: Conventional teacher-centered instruction often limits students’ creative engagement, resulting in low achievement in short story composition. Knowledge Gap: Empirical evidence on structured student-centered approaches, particularly the inductive method, in elementary short story writing remains limited. Aims: This study aimed to examine the application of the inductive method in improving short story writing among fifth-grade elementary students. Results: Using a quantitative one-group pretest–posttest design with 17 participants, the average score increased from 69.7 before instruction to 86.5 after instruction, with a paired t-test yielding p = 0.000, indicating a statistically significant difference. Group discussions, contextual reading materials, and the teacher’s facilitative role supported students’ imagination and idea development. Novelty: The study demonstrates how an inductive, observation-to-generalization learning sequence can foster active participation and creative narrative construction in young learners. Implications: The inductive method offers a viable instructional alternative for language teachers seeking student-centered strategies to support creative writing development at the elementary level.Highlights: Students’ scores rose markedly after instructional treatment using an observation-based learning sequence. Collaborative discussion and contextual texts stimulated imagination and narrative development. Facilitator-oriented teaching supported active participation during the writing process. Keywords: Inductive Method; Short Story Writing; Elementary Education; Creative Writing; Student-Centered Learning